Produktivitas Alat Berat Concrete Pump dengan Perbandingan Elevasi Pengecoran - Dwi Cahya, Maulana Zidan; Prasetyo, Dimas Bagus; Wibisana, Hendrata; Eka Putri, Karina Meilawati (Jurnal Talenta Sipil, 2025)
Construction projects are influenced by various factors, one of which is the productivity of heavy equipment used. One such equipment used in concrete pouring projects is the concrete pump, which functions to transport fresh concrete to the pouring location. This study aims to measure the productivity and time efficiency of concrete pump usage in the construction of the Aston Inn Hotel in Lumajang. The equipment's productivity is calculated based on the volume of concrete pumped and the time required for the pouring process. The results showed that the productivity of the concrete pump on the 5th floor was 0.219 m³/min, while on the 6th floor, it was 0.166 m³/min, with an elevation difference of 3.4 meters between the floors. Time efficiency was also measured, with the pouring of 63 m³ of concrete taking between 30 and 45 minutes, depending on the proximity of the concrete mixer truck to the project site. This study provides insights into how optimizing the use of heavy equipment can improve productivity and efficiency in construction projects, especially in concrete pouring tasks with a concrete pump.